Ethics, Behaviors, and Characters of Memayu Hayuning Bawono, Ambrasto Dur Hangkoro Accountant in Java - I Made Laut Mertha Jaya; Tjiptohadi Sawarjuwono; Sungkono - Sungkono; Mar'a Elthaf Ilahiyah (Universitas Swadaya Gunung Jati, 2021)
AbstractThe moral teachings and philosophy of life of the Javanese have a very deep meaning which leads to happiness. This paper aims to provide up-to-date knowledge about the meaning of Ethics, Behavior, and Character of Memayu Hayuning Bawono, Ambrasto dur Hangkoro in accounting profession education in Java, based on Javanese philosophy. This study uses a qualitative method approach, ethnography. The results of this study conclude that ethics, behavior, and character in accounting profession education based on Javanese philosophy are more bars, ruruh, wantah, duga prayoga, nastiti and do not focus on ardana. The character of